Men's perceptions and preferences regarding prostate cancer radiation therapy: A systematic scoping review. (January 2023) - Brown, Amy; Yim, Jackie; Jones, Scott; Tan, Alex; Callander, Emily; Watt, Kerrianne; De Abreu Lourenco, Richard; Pain, Tilley
Highlights: Patient perceptions are important in addition to clinical and technical considerations. This scoping review found a paucity of prostate cancer patient perception literature. Twenty-seven articles covered pre-, during and post-treatment pathway phases. 5 Main themes were: experiences, information, side effects, preferences and support. Abstract: Purpose: To assess the literature on men's preferences and perceptions regarding prostate cancer radiation therapy. Methods: A scoping review was undertaken as per JBI guidelines. Searches were conducted in PubMed, CINAHL, Scopus and Science Direct with search terms including "prostate cancer, " "radiotherapy, " "radiation therapy, " "radiation oncology, " "patient preferences, " "patient perceptions" and "patient experience." The resultant studies were mapped and grouped according to the emergent themes and pathway stages. Results: A total of 779 titles and abstracts were screened by two independent reviewers. Fifty-two full-text studies were reviewed, with 27 eligible for inclusion. There were 4 pre-treatment, 13 during treatment and 10 post-treatment studies covering broad themes of information needs (n = 3), preferences and decisions (n = 6), general experiences (n = 8), side effects (n = 6), and support (n = 4). There were a mix of methodologies, including 11 qualitative, 14 quantitative (including four preference studies), one mixed methods and one narrative review. Conclusion: There were only four preference studies, with the remaining 23 reporting on perceptions. Overall, there is a paucity of literature regarding patient preferences and perceptions of prostate cancer radiation therapy, particularly when considering how many clinical and technical studies are published in the area. This highlights opportunities for future research.